MIT SPRUCHEN VOLLE BRINGEN: ULRICH VON TÜRHEIM’S AND HEINRICH VON FREIBERG’S PROVER-BIAL STRATEGIES - V. Trokhimenko, Olga (Proverbium - Yearbook, 2018)
The article examines the use of paremiological material in the two thirteenth-century Middle High German versions of the Tristan and Isolde legend by Ulrich von Türheim (ca. 1240–1260) and Heinrich von Freiberg (ca. 1290). Though working with the same originals and facing the same challenge of continuing the story whose ethos neither author could fully embrace, the two poets approach their source material in starkly different ways, based on their individual poetic goal, capabilities, and style. By looking at the way the two poets use proverbs and proverbial expressions in their respective epics, the paper claims that it is representative of their overall treatment of the Tristan story.